RETRACTED: STK35 Gene Therapy Attenuates Endothelial Dysfunction and Improves Cardiac Function in Diabetes - Joladarashi, Darukeshwara; Zhu, Yanan; Willman, Matthew; Nash, Kevin; Cimini, Maria; Thandavarayan, Rajarajan Amirthalingam; Youker, Keith A.; Song, Xuehong; Ren, Di; Li, Ji; Kishore, Raj; Krishnamurthy, Prasanna; et al. (Frontiers in Cardiovascular Medicine, 2022)
Diabetic cardiomyopathy (DCM) is characterized by microvascular pathology and interstitial fibrosis that leads to progressive heart failure. The mechanisms underlying DCM pathogenesis remain obscure, and no effective treatments for the disease have been available. In the present study, we observed that STK35, a novel kinase, is decreased in the diabetic human heart. High glucose treatment, mimicking hyperglycemia in diabetes, downregulated STK35 expression in mouse cardiac endothelial cells (MCEC). Knockdown of STK35 attenuated MCEC proliferation, migration, and tube formation, whereas STK35 overexpression restored the high glucose-suppressed MCEC migration and tube formation. Angiogenesis gene PCR array analysis revealed that HG downregulated the expression of several angiogenic genes, and this suppression was fully restored by STK35 overexpression. Intravenous injection of AAV9-STK35 viral particles successfully overexpressed STK35 in diabetic mouse hearts, leading to increased vascular density, suppression of fibrosis in the heart, and amelioration of left ventricular function. Altogether, our results suggest that hyperglycemia downregulates endothelial STK35 expression, leading to microvascular dysfunction in diabetic hearts, representing a novel mechanism underlying DCM pathogenesis. Our study also emerges STK35 is a novel gene therapeutic target for preventing and treating DCM.